2D materials graphene and hBN boost DMFC performance. Issue 4 (April 2017) - Balakrishnan, Prabhuraj; Holmes, Stuart
Abstract : New research at the University of Manchester in the UK has reported on the use of the 2D materials graphene (monolayer carbon) and hexagonal boron nitride (hBN) in operating direct methanol fuel cells, in which their negligible resistance to protons enhances the fuel cell performance. This opens up a key bottleneck for the commercialisation of fuel cells.